Fishing Areas and Fish Catch Species of Traditional Fishermen in the East Monsoon in the Arafura Waters of Merauke Regency - Welliken K, Marius.A.Welliken K; Maturbongs, Modesta Ranny; Randi, Randi (Agrikan Jurnal Agribisnis Perikanan, 2025)
This study aims to determine the capture area and fish catch in Arafura waters carried out by traditional fishermen on the coast of Lampu Satu Beach, Merauke Regency in the east monsoon. This research was conducted for three months from May to July 2023 in the Arafura Waters of Merauke Regency. Data collection was done by survey method. Oceanographic factors of sea surface temperature, chlorophyll-a, and depth have a relationship to fish catches in the Arafura Waters of Merauke Regency. The potential fishing zone in the Arafura waters of Merauke is at an optimum temperature of 26.71 to 29.85 ?C with optimum chlorophyll-a density distribution between 2.6 mg/m³ to 5.53 mg/m³. The highest abundance of fish in the potential zone was in July with the highest catch of 200 kg.